Las tecnologías de información y comunicación (Tic’s) y su aporte a la actividad secretarial de la Unidad de Estudios a Distancia de la Universidad Técnica Estatal de Quevedo, del cantón Quevedo, provincia de Los Ríos, año 2015 - Aguayo Álvarez, Lucia Alejandra (2015)
This work was developed in the Distance Studies Unit Quevedo, tate Technical University located in the province of Los Rios, Quevedo Canton. It was to determine the contribution of Information Technology and Communication (ICT) in the secretarial activities of the Distance Studies Unit. Inductive-deductive method was used because it allowed the search for elements that facilitated the design of the proposal for this book on the contents of the Information Technology and Communication, administration, telecommunications, and others were used as the primary basis. Mechanisms were sought to facilitate the design of the proposed one such mechanism was the deductive method as books on ICT, administration, telecommunications and the different technological tools were reviewed. Factors impact on the problem analyzed through surveys of students UED. 79% of students of the Distance Learning Unit reside in different provinces of the country and know the procedure to be performed for different procedures, with greater problems in apprenticeships because they do not know whom to direct that communication Coordinators are always rotating, so that they agree with the implementation of a tool and avoid paperwork and mobilizing their hometown to the offices of the Distance Learning Unit. It is recommended to host the attached proposal entitled "Design of methodological structure Workflow as a tool for administrative procedures to expedite students' academic studies Unit Distance procedures". Keywords: ICT, secretarial activities, processes, automation